Lactobacillus fermentum ZS40 Ameliorates Inflammation in Mice With Ulcerative Colitis Induced by Dextran Sulfate Sodium - Chen, Zixia; Yi, Long; Pan, Yanni; Long, Xingyao; Mu, Jianfei; Yi, Ruokun; Zhao, Xin (Frontiers in Pharmacology, 2021)
Colitis is an inflammatory disease of the gut that can caused by many reasons and can even develop into colon cancer.Probiotics are normal bacteria that exist in the human body and have been proven to regulate the balance of intestinal flora and alleviate inflammation. The current study aimed to study the effect of ZS40 on DSS-induced colitis mice. We evaluated the preventive effect of Lactobacillus fermentum ZS40 (ZS40) on dextran sulfate sodium (DSS)-induced colitis in mice. We measured the length and weight of the colon in mice, observed the histopathological morphological changes of the colon, and evaluated the effect of ZS40 on colitis in mice by biochemical kit, ELISA kit, Real-time fluorescence-based quantitative PCR and western blot. We found that ZS40 could reduce inflammatory cell infiltration and goblet cell necrosis in the colon; increase the total superoxide dismutase and catalase in mouse serum; and reduce myeloperoxidase and malondialdehyde levels. ZS40 could downregulate proinflammatory cytokines levels; and upregulate Anti-inflammatory cytokines level. More importantly, ZS40 downregulated the relative expression of nuclear factor-κB p65 (NF-κBp65), IL-6, and TNF-α mRNA and protein, upregulated the relative expression of nuclear factor of κ-light polypeptide gene enhancer in B-cells inhibitor-α (IκB-α), and downregulated the relative expression of p38 and JNK1/2 mRNA and p38, p-p38, JNK1/2, and p-JNK1/2 proteins by regulating the NF-κB and MAPK pathways. Our study suggested that ZS40 may serve as a potential therapeutical strategy for colitis.